Intrascleral Prosthesis in a Dog - Evisceration and Implantation - Guimarães, Tarcísio Guerra; Mamede, Fabricio Villela; Junior, Emilio Fernandes Rodrigues; Pimenta, Paulo; Cardoso, Karla Menezes (Acta Scientiae Veterinariae, 2022)
Background: There is no hope of preserving vision at the terminal stage of glaucoma, and surgical treatment is indicated in these cases. Among the various surgical techniques used, eye evisceration with implantation of an intrascleral prosthesis provide the best cosmetic results. Even though eye evisceration with prosthesis implantation represents an excellent treatment option for terminal glaucoma, reports on the use of this technique in dogs are scarce in the current literature. The aim of this work is to report a case of a dog with end-stage glaucoma subjected to eye evisceration surgery and implantation of an intrascleral prosthesis. Case: A 7-year-old bitch mixed breed with a history of glaucoma secondary to uveitis with no response to medical therapy was referred to the Ophthalmology service of the University Veterinary Hospital of Coimbra (HVUC), Portugal At the ophthalmic examination, the glaucomatous left eye was buphthalmic, with congested episcleral blood vessels, mydriasis, and posterior luxation of the lens; there was no response to threat or obfuscation, no direct and consensual pupillary reflex, nor pupillary reflexes to chromatic light. The intraocular pressure (IOP) was 55 mmHg, and the Schirmer’s tear test (STT-1) result was 19 mm/min. Ophthalmoscopy revealed attenuated retinal blood vessels and a pale optic papilla with mild excavation. The right eye was functional, with all parameters assessed on examination and by tests within the normal ranges for the species. An ultrasound examination of the left eye confirmed the presence of posterior luxation of the lens and buphthalmia in the absence of intraocular neoplasm. In view of the patient’s history and results of the clinical examinations, a surgical approach was indicated to treat the glaucomatous eye. The patient’s tutor requested a surgical procedure that produced a more natural aspect; therefore, the procedure chosen was evisceration, with implantation of an intrascleral prosthesis. The prosthesis diameter chosen was 2 mm greater than the horizontal diameter of the cornea of the functional eye. After evisceration, a black spherical silicone prosthesis of 20 mm in diameter was implanted through a scleral incision. The eye surface was protected with a nictitating membrane flap. In the postoperative period, the cornea exhibited areas with neovascularization, pigmentation, and fibrosis, with a final aspect of gray to black in color. A reduction in tear production was also observed, with no other lesions on the eye surface or major complications. Discussion: Causes of secondary glaucoma include uveitis, disorders of the lens, and neoplasms, among other alterations. Glaucoma can cause clinical signs such as buphthalmic eyes, congestion of the episcleral blood vessels, and increased IOP with nonresponsive mydriasis. The presence of severe degenerative retinal alterations, such as atrophy and excavation of the optic nerve, causes irreversible loss of vision. Surgical treatment is indicated for end-stage glaucoma cases. Eye evisceration with implantation of a prosthesis involves replacement of the intraocular contents by a silicone sphere 1-2 mm larger than the healthy contralateral eye. Protection of the eye surface may be provided using additional procedures such as the nictitating membrane flap. The scleral incision may reduce corneal sensitivity and, consequently, reduce the tear reflex and cause a reduction in STT-1 values. After implantation of the prosthesis, the cornea may exhibit neovascularization, edema, fibrosis, and pigmentation; these are considered expected corneal reactions in the postoperative period. This surgical technique allows treatment of sore and blind eyes, and its results are more aesthetically pleasant compared to other procedures. Preservation of the eyeball with implantation of the prosthesis produced an excellent aesthetic result, with an appearance very close to natural in the case presented here. Keywords: surgery, glaucoma, intraocular prosthesis, silicone. Título: Prótese intraescleral em um cão - evisceração e implantação Descritores: cirurgia, glaucoma, prótese intraocular, silicone.